2018
DOI: 10.3390/catal8090384
|View full text |Cite
|
Sign up to set email alerts
|

NOx Removal by Selective Catalytic Reduction with Ammonia over a Hydrotalcite-Derived NiFe Mixed Oxide

Abstract: A series of NiFe mixed oxide catalysts were prepared via calcining hydrotalcite-like precursors for the selective catalytic reduction of nitrogen oxides (NOx) with NH3 (NH3-SCR). Multiple characterizations revealed that catalytic performance was highly dependent on the phase composition, which was vulnerable to the calcination temperature. The MOx phase (M = Ni or Fe) formed at a lower calcination temperature would induce more favorable contents of Fe2+ and Ni3+ and as a result contribute to the better redox c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…As can be observed, the isotherm of Fe 85 Ce 10 W 5 -CP-CA(NA1.0) can be recognized as a type IV N2 adsorption/desorption isotherm according to the International Union of Pure and Applied Chemistry (IUPAC) classification, and it presents mainly meso-pores (2-50 nm), however, the hysteresis loops of Fe85Ce10W5-CP-CA(NA1.0) and Fe85Ce10W5-CP-CA are the H2 and H1 type [32,34], respectively. This demonstrates that the removal of nitrate promotes the formation of meso-pores in magnetic, and the Fe85Ce10W5-CP-CA catalyst shows uniform and regular meso-pores, which was confirmed by the results of the pore diameter distribution in Figure 5B [35]. Interesting, the Brunauer-Emmett and Teller (BET) surface area of Fe 85 Ce 10 W 5 -CP-CA was 90.85 m 2 /g, a little smaller than that of Fe 85 Ce 10 W 5 -CP-CA(NA 1.0 ) (93.13 m 2 /g), as shown in Table 2.…”
Section: N 2 Adsorption-desorptionsupporting
confidence: 69%
“…As can be observed, the isotherm of Fe 85 Ce 10 W 5 -CP-CA(NA1.0) can be recognized as a type IV N2 adsorption/desorption isotherm according to the International Union of Pure and Applied Chemistry (IUPAC) classification, and it presents mainly meso-pores (2-50 nm), however, the hysteresis loops of Fe85Ce10W5-CP-CA(NA1.0) and Fe85Ce10W5-CP-CA are the H2 and H1 type [32,34], respectively. This demonstrates that the removal of nitrate promotes the formation of meso-pores in magnetic, and the Fe85Ce10W5-CP-CA catalyst shows uniform and regular meso-pores, which was confirmed by the results of the pore diameter distribution in Figure 5B [35]. Interesting, the Brunauer-Emmett and Teller (BET) surface area of Fe 85 Ce 10 W 5 -CP-CA was 90.85 m 2 /g, a little smaller than that of Fe 85 Ce 10 W 5 -CP-CA(NA 1.0 ) (93.13 m 2 /g), as shown in Table 2.…”
Section: N 2 Adsorption-desorptionsupporting
confidence: 69%
“…Just as the catalytic results presented, the Ni 3 Mn 1 Fe 1 ‐600 catalyst showed the most satisfactory DeNO x results. It can be seen from Figure S2 that the DeNO x efficiency of NiMnFe−T catalysts was better at low temperature range than NiFe‐LDO catalyst of our previously reported, which should be ascribed to Mn species redox behavior . Furthermore, the effect of GHSV on the DeNO x performance of Ni 3 Mn 1 Fe 1 ‐600 catalyst was also investigated Figure S3, ESI†).…”
Section: Resultsmentioning
confidence: 73%
“…Besides, it was also discovered that the strong interaction between the Ni and Mn species in the NiMn bi‐metal oxides could lead to great catalytic activities of NO x removal . Apart from that, our preliminary research found that NiFe mixed oxide afforded superior SO 2 resistance and catalytic stability in the application of NH 3 ‐SCR due to the creation of redox cycle resulting from the electron transfer between Ni and Fe, whereas the low‐temperature DeNO x activity was not very satisfactory . Thus, introducing Mn species into the NiFe system might be promising to improve NH 3 ‐SCR activity in the low temperature zone.…”
Section: Introductionmentioning
confidence: 89%
“…In the automotive industry, hydrocarbons are initially preferred as reductors as they are present in the exhaust gas, but not many catalysts are active for the reaction and most of them have problems related to the hydrothermal stability of the materials [7]. Ammonia is the other alternative selected by the industry and a high efficiency [8,9] can be obtained when ammonia or its precursor (urea) are used for the NO x -SCR.…”
Section: Introductionmentioning
confidence: 99%